EVIDENCE FOR SUBDUCTION-RELATED COMPONENTS IN THE SUBCONTINENTAL MANTLE FROM LOW 3HE/4HE AND 40AR/36AR RATIO IN MANTLE XENOLITHS FROM FAR EASTERN RUSSIA - Yamamoto J.; Kaneoka I.; Nakai S.; Kagi H.; Prikhod'ko V.; Arai S. (My University, 2004)
By applying both vacuum crushing and stepwise heating methods for the extraction of the noble gases, we have discovered ³He/⁴He ratios much lower than the atmospheric ratio (∼0.3 RA; RA is the atmospheric ³He/⁴He ratio of 1.4×10⁻⁶) and relatively low ⁴⁰Ar/³⁶Ar ratios (<1000) in olivine separates from some subcontinental mantle-derived xenoliths from Far Eastern Russia. The low ³He/⁴He ratios cannot be explained by the addition of radiogenic ⁴He generated in-situ after the eruption of magma entraining the xenoliths. Furthermore, petrographic evidence suggests that incorporation of crustal fluids is not likely. Hence, it must reflect a feature of the Far Eastern Russian upper mantle.